Efficacy of a compulsory homework programme for increasing physical activity and healthy eating in children: the healthy homework pilot study - Duncan Scott; McPhee Julia C; Schluter Philip J; Zinn Caryn; Smith Richard; Schofield Grant (BMC, 2011)
Abstract Background Most physical activity and nutrition interventions in children focus on the school setting; however, evidence suggests that children are less active and have greater access to unhealthy food at home. The aim of this pilot study was to examine the efficacy of a compulsory homework programme for increasing physical activity and healthy eating in children. Methods The six-week 'Healthy Homework' programme and complementary teaching resource was developed under the guidance of an intersectoral steering group. Eight senior classes (year levels 5-6) from two diverse Auckland primary schools were randomly assigned into intervention and control groups. A total of 97 children (57 intervention, 40 control) aged 9-11 years participated in the evaluation of the intervention. Daily step counts were monitored immediately before and after the intervention using sealed multiday memory pedometers. Screen time, sports participation, active transport to and from school, and the consumption of fruits, vegetables, unhealthy foods and drinks were recorded concurrently in a 4-day food and activity diary. Results Healthy Homework resulted in a significant intervention effect of 2,830 steps.day-1 (95% CI: 560, 5,300, P = 0.013). This effect was consistent between sexes, schools, and day types (weekdays and weekend days). In addition, significant intervention effects were observed for vegetable consumption (0.83 servings.day-1, 95% CI: 0.24, 1.43, P = 0.007) and unhealthy food consumption (-0.56 servings.day-1, 95% CI: -1.05, -0.07, P = 0.027) on weekends but not weekdays, with no interactions with sex or school. Effects for all other variables were not statistically significant regardless of day type. Conclusions Compulsory health-related homework appears to be an effective approach for increasing physical activity and improving vegetable and unhealthy food consumption in children. Further research in a larger study is required to confirm these initial results.